(untitled) (Al-Farooq Journal of Sciences, 2026)
in this paper, we define a new generalized multi- parameter differential operator. This operator generalize many well-known operators studied earlier by famous authors. Also, new subclasses of starlike and convex functions will be introduced based on the new operator. Further, some general properties for the new subclasses will be studied.